2014
DOI: 10.1111/imre.12144
|View full text |Cite
|
Sign up to set email alerts
|

The International Migration Review at 50: Reflecting on Half a Century of International Migration Research and Looking Ahead

Abstract: When the International Migration Review was established half a century ago, international migration was a peripheral area of research, and migration issues were far less prominent on policy agendas than they are today. This essay introduces the 50th Anniversary Issue of the International Migration Review and begins by identifying seven main areas of change in migration research and migration trends during the journal's lifetime. Subsequently, we examine changes in the geographical distribution of authorship of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 67 publications
0
15
1
Order By: Relevance
“…Feminization of migration has been documented since a long time ago (Castles and Miller 1993). As women increase their share among international migrants, scholars expected to see gender becoming a prominent category in future migration studies (Lee et al 2014). Despite these expectations, we have not observed an increase in the number of articles that categorised migrants with respect to gender categories.…”
Section: Categorisation Of Migrantscontrasting
confidence: 63%
“…Feminization of migration has been documented since a long time ago (Castles and Miller 1993). As women increase their share among international migrants, scholars expected to see gender becoming a prominent category in future migration studies (Lee et al 2014). Despite these expectations, we have not observed an increase in the number of articles that categorised migrants with respect to gender categories.…”
Section: Categorisation Of Migrantscontrasting
confidence: 63%
“…Discrimination and immigrants' psychological well-being Lee et al (2014) stated that despite broad changes in immigration-related issues over the past 50 years, immigrants continue to experience discrimination in their daily lives. Discrimination is closely related to immigrants' attainment of their objectives (e.g., occupational attainment) and affects their psychological well-being (Alba and Nee, 2005;Borjas, 1999Borjas, , 2006Portes and Rumbaut, 2006;Zhou, 1997).…”
Section: Immigrants In Japanmentioning
confidence: 99%
“…The literature on migration is vast and diverse (a decent review of migration research could be found in Lee et al 2014). A strand of it, e.g.…”
Section: Introductionmentioning
confidence: 99%